Efficiency enhancement of Sb2Se3 thin-film solar cells by the co-evaporation of Se and Sb2Se3. (7th April 2016) - Li, Zhiqiang; Zhu, Hongbing; Guo, Yuting; Niu, Xiaona; Chen, Xu; Zhang, Chong; Zhang, Wen; Liang, Xiaoyang; Zhou, Dong; Chen, Jingwei; Mai, Yaohua
Abstract: In this work, we present an alternative route to supply excessive selenium (Se) for the deposition of Sb2 Se3 thin films by the co-evaporation of Se and Sb2 Se3 . Scanning electron microscopy (SEM) images showed that additional Se modified the growth process and surface morphology of Sb2 Se3 thin films. X-ray diffraction (XRD) patterns confirmed that this co-evaporation process enhanced the beneficiary preferred orientations, and capacitance–voltage ( C – V ) measurement showed that the carrier concentration of the Sb2 Se3 absorber increased with the additional evaporation of Se. Accordingly, the efficiency of the devices employing co-evaporated Sb2 Se3 absorber layers increased significantly from 2.1 to 3.47% with a open-circuit voltage ( V OC ) of 364 mV, a short-circuit current density ( J SC ) of 23.14 mA/cm 2, and a fill factor (FF) of 41.26%.